Development of a Diagnostic Tool to Benchmark Best Manufacturing Practices in Malaysian SMEs - Abdul Aziz, Mariam (2007)

(untitled)
In developing countries such as Malaysia, the small and medium scale enterprises (SMEs) play an important role in increasing the country’s economy. For the SMEs to remain competitive and to ensure their survival in the globalize era, the SMEs must continuously improve their manufacturing practices. The development of self assessment tool can facilitate the SMEs to benchmark their manufacturing practices and will help them in becoming more competitive. Based on literature review, eight areas of manufacturing practices have been proposed for benchmarking and the areas have been validated by selected companies. The areas of manufacturing practices included in this tool are management practice, human resource, marketing strategy, quality, production process, customer focus, supply chain management, technology and product innovation.The development of this web-based tool used the Hypertext Preprocessor (Php), Structured Query Languages (SQL) scripting languages and Internet as a platform. The participating SMEs can log into the system and choose a particular area to be benchmarked. Based on the indicators that have been developed, summary of their performance and how they fare with others will be generated in the form of a graph. The graph clearly indicates the gaps in their practices. The SMEs can then make appropriate decisions on which areas to be improved, with those results. The benchmarking tool system has been tested and validated by seven SMEs. From the companies’ feedback, some improvements and modifications have been made on the system such as questionnaires, output results and company registration form. The system was developed in dual language (Malay and English) to facilitate SMEs benchmark in the company. It is hoped that the SMEs using this tool will become more aware of the importance of certain practices, facilitate SMEs to be more competitive and able to develop a culture of continuous improvement.